Implementation for Improving SDN Efficiency with The ML Algorithm, RF - Singh, Saroj; Sharma , Dr. Kamlesh (International Journal of Basic and Applied Sciences, 2025)
Software-Defined Networking (SDN) offers unprecedented profitability and centralized control over network infrastructure, yet optimizing ‎its efficiency, particularly in dynamic and complex environments, remains a significant challenge. Traditional network management often ‎struggles with real-time traffic classification and resource allocation, leading to congestion and suboptimal performance. The paper proposes a ‎novel approach to enhance SDN efficiency through the integration of a Random Forest machine learning model for intelligent traffic classi‎fication and proactive resource management. We leverage the Random Forest’s ability to handle high-dimensional data, identify complex ‎patterns, and provide robust predictions for various traffic types. Our methodology involves collecting network flow data from an emulated ‎SDN environment, extracting relevant features, training the Random Forest model for accurate traffic categorization (e.g., critical, best-effort, ‎delay-sensitive), and subsequently using these classifications to inform the SDN controller’s decisions on dynamic path allocation, load ‎balancing, and Quality of Service (QoS) enforcement. Experimental results demonstrate that the Random Forest model significantly ‎improves network throughput, reduces latency, and enhances overall resource utilization compared to traditional rule-based or less intelligent ‎approaches in SDN. This research contributes to the growing body of knowledge on applying machine learning to optimize modern network architectures‎.